1998
DOI: 10.1023/a:1008343219970
|View full text |Cite
|
Sign up to set email alerts
|

The cognitive-spiritual dimension – an important addition to the assessment of quality of life: Validation of a questionnaire (SELT-M) in patients with advanced cancer

Abstract: Overall there is confirming evidence for the hypothesised structure of the SELT-M, especially for the newly developed module on spiritual QL. This module may be used as a module together with other cancer specific QL questionnaires.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2004
2004
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 13 publications
0
18
0
2
Order By: Relevance
“…To evaluate the spiritual well-being, we used the SELT-M (Skalen zur Erfassung von Lebens qualitat bei Tumorkranken-Modified Version) [22], because at the time of this investigation, no other validated measurement tools to assess spiritual well-being were available in Japan. The patients completed the Japanese version of the SETL-M [13] before and after the intervention.…”
Section: Interventions and Outcome Measurementsmentioning
confidence: 99%
“…To evaluate the spiritual well-being, we used the SELT-M (Skalen zur Erfassung von Lebens qualitat bei Tumorkranken-Modified Version) [22], because at the time of this investigation, no other validated measurement tools to assess spiritual well-being were available in Japan. The patients completed the Japanese version of the SETL-M [13] before and after the intervention.…”
Section: Interventions and Outcome Measurementsmentioning
confidence: 99%
“…This concerns questions of meaning or possible positive aspects and experiences related to the disease, coping with issues of life and death, finding new inner goals, interests and hope beyond the physical perspective of life, having more courage to be oneself, and the ability to distinguish the essential from the non-essential. The resulting SELT-M contains 5 functional scales: 'physical well-being' (3 items), 'basic mood' (6 items), 'social support' (3 items), 'inner life orientation' (3 items) and the newly added 'spiritual QoL' (8 items), which had shown good construct and discriminant validity [24]. As the item contents of 'inner life orientation' and 'spiritual QoL' are very closely related, and as both dimensions with their cognitive and spiritual elements pertain to the spiritual aspects of human being in the perspective of AM, we combined them for evaluation for the present publication to form the dimension 'cognitive-spiritual QoL' (13 items).…”
Section: Assessment and Evaluation Of Qolmentioning
confidence: 99%
“…Yet, so far, the effectiveness of its holistic therapeutic strategy has not been studied systematically. Therefore, the LK was included in a composite research project of the Swiss National Science Foundation Program NFP 34, which we reported about earlier [14,[22][23][24][25][26][27]. The aim was a first and thorough investigation of QoL development in patients with advanced cancer during and after holistic in-patient treatment at LK.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years the traditionally assessed aspects of quality of life (QOL) such as physical, psychological and social well-being and functioning have been supplemented by spiritual aspects of QOL [1,2,3]. The importance of spirituality as a central component of psychological wellbeing is increasingly recognized by doctors and mentalhealth professionals [4].…”
Section: Introductionmentioning
confidence: 99%